Job Satisfaction Among Academicians in Nepal: The Influence of Institutional Sector and Demographic Factors - Bal Ram Chapagain (Quantitative Economics and Management Studies, 2021)
Considering the importance of job satisfaction in teaching, and the ongoing debate regarding the influence of various factors on job satisfaction, this study identifies the status of job satisfaction and examines the influence of institutional sector and demographic factors on job satisfaction among Nepalese academicians. The study sample comprised 156 academicians from different higher-level educational institutions in Nepal, and the data were collected through structured questionnaires. Descriptive statistics, independent-samples t-test, and one-way ANOVA test were used to analyze the data. Results showed that Nepalese academicians are moderately satisfied with their job, in which intrinsic factors appear stronger than extrinsic factors. The findings also demonstrated that the institutional sector, in favor of public institutions, and academic qualification influence job satisfaction but gender, age, and teaching experience do not influence job satisfaction of academicians. Widespread sampling framework, all-inclusive job satisfaction measures, and remarkable findings have made the study unique and potent.